Plant Cell Wall-Like Soft Materials: Micro- and Nanoengineering, Properties, and Applications - Roya Koshani; Mica L. Pitcher; Jingyi Yu; Christine L. Mahajan; Seong H. Kim; Amir Sheikhi (Nano-Micro Letters)
Highlights This review provides a detailed account of engineered plant cell wall (CW)-mimetic soft materials, which are designed to replicate the intricate composition, structure, and mechanical properties of natural plant CWs. Experimental methods to create CW-like materials are reviewed, and relevant characterization techniques, including mechanical, chemical, structural, and morphological analyses, are discussed.  The applications of CW-like materials in several fields, including food packaging, edible films, drug delivery, construction materials, and biocatalysis are highlighted.